Pengaruh Gamifikasi Menggunakan Quizziz Terhadap Motivasi Belajar Trigonometri Siswa SMAS Sandikta - Diva Ceriana Phindo Connery; Edah Jubaedah; Muhammad Ihsan Saladin; Arinda Yulistiyani; Stevani Priscila; Eka Septiani (Lembag, 2025)
This study aims to analyze the relationship between Quizizz gamification and students' learning motivation in Trigonometry, a subject often considered difficult, at Sandikta High School. Using a correlational survey method, data from Quizizz scores (X variable) and an ARCS model-based motivation questionnaire (Y variable) were quantitatively analyzed. The Pearson correlation analysis revealed a very strong, positive, and significant relationship (). The resulting regression equation is y=41+0.37x, with a coefficient of determination (R2) of 0.6946. This indicates that 69.46% of the variance in learning motivation can be explained by Quizizz scores, highlighting the platform as a potential tool for enhancing student motivation in facing challenging subjects.